Electronics with discrete components - Galvez, Enrique Jose, 1956- (Danvers, MA : John Wiley & Sons, Inc., 2013)
"Designed for a one semester course on electronics for physics and science majors, this text offers a comprehensive, up-to-date alternative to currently available texts by providing a modern approach to the course. It includes the mix of theory and practice that matches the typical electronics course syllabus with balanced coverage of both digital and analog electronics"--
Machine generated contents note: 1 The Basics. 2 Introduction to Digital Electronics. 3 Combinational Logic. 4 Advanced Combinational Devices. 5 Sequential Logic. 6 AC Signals. 7 Filters and the Frequency Domain. 8 Diodes. 9 Transistors. 10 Operational Amplifiers. 11 Connecting Digital to Analog and to the World.
Includes index.
Keywords: Electronics -- Textbooks; Digital electronics -- Textbooks; Analog electronic systems -- Textbooks; SCIENCE / Solid State Physics